OPTIMALISASI KUALITAS PELAYANAN MELALUI KOMUNIKASI INTERPERSONAL PEGAWAI - Aminah, Siti; Marhendra, R. Agus; Biongan, Ahiar; Mukdin , Novita B.; Tabo, Sarfan (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This research aims to play a key role in the decision-making process. Open and constructive discussions between employees can help in formulating policies and making better decisions in the interests of society. Simamora, F. N. (2018) emphasized that kStrong interpersonal communication allows employees to share information, ideas and views with each other. This can help in identifying and solving problems that may arise in public services or operations. The aim of this research is to provide a valuable contribution to the development of science, especially those related to interpersonal communication in improving the quality of work of employees in Bintauna District, North Bolaang Mongondow Regency. It is hoped that this research will be able to expand and enrich knowledge regarding communication science and qualitative research in the field of communication, especially interpersonal communication. R. Wayne Pace (2017) stated interpersonal communication or interpersonal communication. The implication of this research is that the quality of internal information systems has not been emphasized too intensely in meeting organizational goals. This can be caused by various factors, including a lack of collaboration between different systems, a lack of accurate monitoring of operational data through the information system provided by the sub-district, as well as a lack of systematic and ongoing performance evaluation. Apart from that, mastery of communication media and digitalization of technology-based information systems have not been widely implemented. In conclusion, the quality of service through interpersonal communication has been running optimally, but it is still a manual process. So with the acceleration of digitalized services, the Bintauna sub-district office still has to adjust to the new pattern.